Evidence for subduction-related signatures in the southern African lithosphere from the N-O isotopic composition of metasomatic mantle minerals. (1st December 2019) - Fitzpayne, Angus; Giuliani, Andrea; Harris, Chris; Thomassot, Emilie; Cheng, Chen; Hergt, Janet
Abstract: Current understanding of the fate of subducted material (and related fluids) in the deep Earth can be improved by combining major and trace element geochemistry with stable isotopic compositions of mantle rocks or minerals. Limited isotopic fractionation during high temperature processes means that significant deviations from mantle-like isotope ratios in mantle rocks probably result from recycling of surficial material. To determine the effects and origins of mantle metasomatic fluids/melts, new δ 15 N and δ 18 O data have been collected for thirteen mantle xenoliths – harzburgites, wehrlites, lherzolites, and MARID (Mica-Amphibole-Rutile-Ilmenite-Diopside) rocks – from the Bultfontein kimberlite (Kimberley, South Africa), which show varying degrees of metasomatism. The δ 18 O values of olivine and orthopyroxene in phlogopite-free harzburgites match the mantle composition (δ 18 Oolivine  = +5.2 ± 0.3‰; δ 18 Oorthopyroxene  = +5.7 ± 0.3‰; 2 s.d.), consistent with previous inferences that harzburgites were formed by interaction with ancient silica-rich melts unrelated to subduction processes. Wehrlite samples display mineral compositional characteristics (e.g., low La/Zr in clinopyroxene) resembling those of other products of kimberlite melt metasomatism, such as PIC (Phlogopite-Ilmenite-Clinopyroxene) rocks. The inferred interaction with kimberlite melts may be responsible for O isotopic disequilibrium between clinopyroxene and olivine (Δ 18 O = +0.2‰) in the wehrlites of this study. In contrast with broadly mantle-like δ 18 O values, the δ 15 N value of phlogopite in a wehrlite sample (+5.9‰) differs from the mantle composition (δ 15 N = −5 ± 2‰). This unusual N isotopic composition in kimberlite-related mantle products might indicate that a recycled crustal component occurred in the source of the Kimberley kimberlites, or was assimilated during interaction with the lithospheric mantle. Similar major and trace element characteristics in clinopyroxene from phlogopite-lherzolite and MARID samples suggest metasomatism by fluids of similar composition. Lherzolite and MARID clinopyroxene δ 18 O values (as low as +4.4‰) extend below those reported in mantle peridotites (i.e. δ 18 Oclinopyroxene  = +5.6 ± 0.3‰; 2 s.d.), and strong negative correlations are found between mineral δ 18 O values and major element compositions (e.g., Na2 O contents in clinopyroxene). Furthermore, phlogopite δ 15 N values (+4 to +7‰) in the studied lherzolite and MARID samples are higher than mantle values. Combined, the low δ 18 O-high δ 15 N isotopic signatures of MARID and lherzolite samples suggest progressive mantle metasomatism by a melt containing a recycled oceanic crust (eclogitic) component. This study demonstrates that progressive enrichment of the subcontinental lithospheric mantle may be inextricably linked to plate tectonics via recycling of subducted crustal material into the deep mantle.